American Political Pamphlets 1917-1945 at the British Library - Jodie Collins (Electronic British Library Journal, 2022)
The twentieth century was a golden age of pamphleteering in America, especially during the period between the Russian Revolution of 1917 and the conclusion of the Second World War in 1945. Pamphlets were vital tools for radical organizations in educating and communicating with their own members and persuading the public of the righteousness of their cause. Though some pamphlets could be obtained free of charge, they were usually sold at a low cost. Among the many modern pamphlets held by the British Library is a modest assortment of American political pamphlets, which have been collated to help researchers and the public to more easily discover and engage with this fascinating material.